Jean Jacques Rousseau as a constitutionalist. His projects for Corsica and the Polish-Lithuanian commonwealth (part II) - Filipiak, Zbigniew (The Opole Studies in Administration and Law, 2020)
The article is a continuation of the dissertation on constitutional projects of Jean Jacques Rousseau. The first part concerned his reform work for Corsica, while the second part presents concepts prepared for the Polish-Lithuanian Commonwealth. Both projects were written for a specific orders – from a Corsican conservative nobleman Mathieu Buttafoco and the Bar Confederates. The comparison of these works, as well as their reference to earlier works by Rousseau, gives the opportunity to look at the evolution of the philosopher’s views, his attempt to adapt them to specific social, political and historical conditions. The less radical tone of the proposals for Poland is noteworthy. It is also necessary to answer the question of what made him want to deal with the affairs of both lands.